Endocrine effect of phthalate metabolites and a butterfly effect of prenatal exposure to androgens on qualitative aspects of female sexual response- an initial survey - Kolena, Branislav; Hlisníková, Henrieta; Nagyová, Miroslava; Orendáčová, Katarína; Vondráková, Mária; Petrovičová, Ida; Mlynček, Miloš; Weiss, Petr; Pfaus, James G (International journal of impotence research, 2025)
There is growing evidence that endocrine disruptive chemicals have deleterious effects on sexual and reproductive function. To examine subjective sexual functions in human females and their relationship to postnatal phthalate exposure and perinatal androgenization, a Sexuality Score (SS) was established from a first-stage survey questionnaire of subjective sexual function filled out by female university students (n = 68; average age 25.23 ± 5.17 years; rural 25.51 ± 6.74 vs. urban 25.85 ± 1.43 years). Seventeen phthalate metabolites in urine samples were analyzed by high-performance liquid chromatography (HPLC) and tandem mass spectrometry (MS/MS). Females were also assessed for the 2D:4D digit ratio as an index of perinatal androgenization. The mean age of menarche was 12.82 ± 1.35 years (rural 12.59 ± 1.39 vs. urban 13.18 ± 1.27; p = 0.01). The mean age at first sexual intercourse was 14.88 ± 6.89 years (rural 14.62 ± 7.20 vs. urban 15.24 ± 6.55), and as the age of first sexual intercourse increases, the SS score tends to increase as well, albeit moderately (r = 0.25, p = 0.037). Mono-iso-butyl phthalate, mono(2-ethyl-5-carboxypentyl) phthalate, mono(hydroxy-n-butyl) phthalate, mono(2-ethyl-5-oxohexyl) phthalate (p ≤ 0.05) and mono(2-carboxymethylhexyl) phthalate (p ≤ 0.01) were negatively associated with SS. A compounding butterfly effect of prenatal exposure to androgens was observed with disruptive effects of mono(2-ethyl-5-oxohexyl) phthalate and mono(2-ethyl-5-carboxypentyl) phthalate on sexual function. Exposure to phthalates in adult females may lead to disruption of subjective sexual function, especially concerning sexual desire and sexual satisfaction, and perinatal androgenization could augment these effects.
Keywords: Phthalic Acids; sexuální chování; Androgens; těhotenství; kyseliny ftalové; mladiství; androgeny; průzkumy a dotazníky; Adult; mladý dospělý; endokrinní disruptory; Young Adult; Sexual Behavior; ženské pohlaví; Endocrine Disruptors; Humans; Pregnancy; Surveys and Questionnaires; zpožděný efekt prenatální expozice; dospělí; Female; Adolescent; Prenatal Exposure Delayed Effects; lidé